Hukum Internasional di era siber: Regulasi atas Kejahatan Digital Lintas Negara - annisa daffa nurlaila (Yayasan Lentera Keadilan Cendikia, 2025)
The advent of digital technology and the internet has opened up new opportunities, butalso brought serious legal challenges, particularly regarding transnational digital crime.Transnational cybercrime presents challenges for law enforcement because it involvesperpetrators located in various countries with different legal systems. This article aimsto analyze existing international regulations, focusing on the Budapest Convention, andthe challenges faced in implementing them in Indonesia. The research method used isa qualitative approach with an in-depth literature review of international and nationallegal documents and regulations related to digital crime. The results show that despitethe existence of international regulations, law enforcement against transnationalcybercrime in Indonesia still faces various obstacles. Improved cooperation betweencountries and regulatory reforms are needed to address this issue more effectively